Content and context in advertising - Pereira, Francisco José Costa (2020)
The content and context of advertising messages have always been a concern of researchers in trying to understand how they were contructed to identify tendencies on advertising and to recognize the processes that make them eficient. Each message conveys meanings contained in the information about products or services, and those values in which they are supported, which is aimed to be transmitted either in an informational or transformational way. Thus, we can state that advetising works as a narrative fiction whose contents are framed by characters and staging that have the final purpose of involving and seducing the consumer. These characters play a fundamental role in transforming the products into symbols and in serving as identification models for consumers. Understanding advertising contents helps us to understand the impact that messages might have.